Evaluation of the effect of combined intralesional injection of prostaglandin F2α with narrow band UVB phototherapy in treatment of resistant cases of vitiligo - Eldelee, Samah A.; Gheida, Shereen F.; Sarhan, Naglaa I.; Ibrahim, Zeinab A.; Elfar, Nashwa N. (The Journal of dermatological treatment, 2021)
Vitiligo is a chronic cutaneous disease characterized with hypopigmented patches that leave psychological impact on the patients. There is increasing need for new treatment modalities to shorten the duration of treatment of vitiligo with the least side effects. To explore the effect of intralesional injection of prostaglandin F2α on the outcome of narrow band ultraviolet rays B (NBUVB) for patients with stable vitiligo. The study included 27 stable vitiligo patients with overall symmetrical lesions. For each patient, one patch was treated with NBUVB alone (control side), while another symmetrical patch was treated with combined intralesional injection of prostaglandin F2α with NBUVB therapy, weekly for 3 months. There was statistically significant improvement in the repigmentation in the combination group compared with NBUVB group. Side effects were minimal. Intralesional injection of prostaglandin F2α in combination with NBUVB therapy could be considered as safe and tolerable technique for treatment of vitiligo, it shortens the duration of NBUVB therapy. Longer follow up is needed.